Development of Gus Dur's perspective religious moderation education module at Ma'had Al-Jami'ah UIN Maulana Malik Ibrahim Malang - Shuhadak Shuhadak; Nurul Hikmah; Makhi Ulil Kirom; M Rofik Fitrotulloh (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Gus Dur contributed brilliant ideas regarding efforts to build awareness of multiculturalism to increase the development of tolerance and heterogeneity in a multicultural society. This idea is known as the nine main values of Gus Dur including monotheism, humanity, justice, equality, brotherhood, liberation, simplicity, chivalry and local wisdom. The purpose of this study is to increase the availability of learning media for insight into moderate values in religion while at the same time helping educators in ma'had, namely the board of caregivers, murrobi/ah and musyrif/ah in providing students with an understanding of moderate Islamic values in the context of religion and Indonesia. As well as being a counter discourse to negative narratives about intolerance and radicalism in the name of religion or ethnicity. This development research uses the ADDIE model, the ADDIE model went through 5 stages of research, namely analysis, design, development, implementation, evaluation. The development of Gus Dur's Perspective Religious Moderation Education at Ma'had al-Jami'ah UIN Maulana Malik Ibrahim Malang obtained very valid criteria. And based on the percentage of the results of field trials, it can be said that the pocket books that have been tested can be said to be effective and feasible to use.